NIKAH SIRI DALAM TINJAUAN FIQIH MUNAKAHAH DAN DAMPAKNYA TERHADAP PERLINDUNGAN HAK PEREMPUAN - Munir, Munir (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2026)
Siri marriage (unregistered marriage) is a marital practice that remains prevalent in Muslim societies and has generated ongoing debate in the field of fiqh munakahah and contemporary Islamic law. Normatively, siri marriage may be considered valid if it fulfills the pillars and conditions of marriage according to Islamic jurisprudence. However, this practice raises serious concerns regarding the protection of women’s and children’s rights due to the absence of state registration and legal recognition. This study aims to analyze siri marriage from the perspective of fiqh munakahah and to examine its impact on the protection of women’s rights. This research employs a library research method, with data collected through documentation of classical fiqh sources, contemporary Islamic legal thought, and relevant statutory regulations. Data analysis is conducted using inductive reasoning and content analysis. The findings indicate that although siri marriage may be formally valid under classical fiqh, it potentially contradicts the objectives of Islamic law (maqāṣid al-sharīʿah), as it creates legal uncertainty and places women in vulnerable positions with regard to maintenance rights, legal protection, and civil rights. Therefore, synergy between fiqh munakahah and national law, particularly through mandatory marriage registration, is essential to strengthen the protection of women’s rights and to realize justice within the institution of Islamic marriage